Lung recruitment before surfactant administration in extremely preterm neonates with respiratory distress syndrome (IN-REC-SUR-E): a randomised, unblinded, controlled trial. Issue 2 (February 2021) - Vento, Giovanni; Ventura, Maria Luisa; Pastorino, Roberta; van Kaam, Anton H; Carnielli, Virgilio; Cools, Filip; Dani, Carlo; Mosca, Fabio; Polglase, Graeme; Tagliabue, Paolo; Boni, Luca; Cota, Francesco; et al.
Summary: Background: The importance of lung recruitment before surfactant administration has been shown in animal studies. Well designed trials in preterm infants are absent. We aimed to examine whether the application of a recruitment manoeuvre just before surfactant administration, followed by rapid extubation (intubate-recruit-surfactant-extubate [IN-REC-SUR-E]), decreased the need for mechanical ventilation during the first 72 h of life compared with no recruitment manoeuvre (ie, intubate-surfactant-extubate [IN-SUR-E]). Methods: We did a randomised, unblinded, controlled trial in 35 tertiary neonatal intensive care units in Italy. Spontaneously breathing extremely preterm neonates (24 + 0 to 27 + 6 weeks' gestation) reaching failure criteria for continuous positive airway pressure within the first 24 h of life were randomly assigned (1:1) with a minimisation algorithm to IN-REC-SUR-E or IN-SUR-E using an interactive web-based electronic system, stratified by clinical site and gestational age. The primary outcome was the need for mechanical ventilation in the first 72 h of life. Analyses were done in intention-to-treat and per-protocol populations, with a log-binomial regression model correcting for stratification factors to estimate adjusted relative risk (RR). This study is registered with ClinicalTrials.gov, NCT02482766 . Findings: Of 556 infants assessed for eligibility, 218 infants were recruited from Nov 12, 2015, to Sept 23, 2018, and included in the intention-to-treat analysis. The requirement for mechanical ventilation during the first 72 h of life was reduced in the IN-REC-SUR-E group (43 [40%] of 107) compared with the IN-SUR-E group (60 [54%] of 111; adjusted RR 0·75, 95% CI 0·57–0·98; p=0·037), with a number needed to treat of 7·2 (95% CI 3·7–135·0). The addition of the recruitment manoeuvre did not adversely affect the safety outcomes of in-hospital mortality (19 [19%] of 101 in the IN-REC-SUR-E group vs 37 [33%] of 111 in the IN-SUR-E group), pneumothorax (four [4%] of 101 vs seven [6%] of 111), or grade 3 or worse intraventricular haemorrhage (12 [12%] of 101 vs 17 [15%] of 111). Interpretation: A lung recruitment manoeuvre just before surfactant administration improved the efficacy of surfactant treatment in extremely preterm neonates compared with the standard IN-SUR-E technique, without increasing the risk of adverse neonatal outcomes. The reduced need for mechanical ventilation during the first 72 h of life might facilitate implementation of a non-invasive respiratory support strategy. Funding: None.